DIABETES MANAGEMENT BASED ON ARTIFICIAL INTELLIGENCE: CONTROLLING GLUCOSE LEVELS THROUGH DIGITAL ASSISTANTS (KIUT Publication, 2025)
Patients with type 1 diabetes (T1D) are required to continuously monitor their blood glucose levels throughout their lives due to insulin deficiency. This condition increases the risk of serious complications such as hypoglycemia or hyperglycemia. In recent years, “artificial pancreas” systems have been developed using continuous glucose monitoring (CGM) sensors and insulin pumps. However, decision-making in these technologies largely remains the responsibility of the patient. Therefore, artificial intelligence, particularly reinforcement learning and decision support systems (DSS), enables automated, personalized, and safe management of diabetes